Cost Analysis of Accidents According to Demographic Factors in Iran - Reza HASHEMPOUR; Ali TAHMASEBI; Mohammad VEYSI; Milad AMINI; Nader TAVAKOLI (Tehran University of Medical Sciences, 2019)
Background: The first cause of death and disability constituting to the burden of disease in Iran has been accident and injury incidents. Young people are more at risk, these accidents have a negative effect on the national gross domestic product (GDP), on the one hand, and they increase the costs of the health system on the other hand. Therefore, this study aimed to analyze the costs and epidemiological pattern of accidents. Methods: The study variables in the first 8 months of 2016 included from Tehran Province, Iran; age, sex, how to transfer to the hospital, consequences of an accident, the injured area, and costs. Overall, 400 cases were investigated by referring to the patients` files and deriving the intended data. SPSS software used to analyze the data and statistical tests of t-test and ANOVA were applied. Results: Most accidents have happened in summer months of Jun, Jul and Aug. Most of the files (48%) were related to the age group of 16-30. The mean cost was 9024.82 dollar. In total, 39% of the road accidents had occurred by motorcycle and 90.8% of the patients discharged from the hospital. Conclusion: Since about half of the traffic accidents were related to the age of 16 to 30 who were the active population of a community, therefore, any disability or death in these groups could cause an economic burden on the community and increase DALY. Thus, it appears essential to develop proper programs such as education for appropriate driving and strict rules for giving driving license to these ages.